An isosceles triangle
A
B
C
with
A
B
=
A
C
has
A
D
as its altitude where
D
is on
B
C
. Let
C
"
be the diametrically opposite point to
C
on the circumcircle of
Δ
A
B
C
and let
M
be the midpoint of
A
B
.
Construct a circle centred at M of radius M C " and let it intersect A B (possibly extended) at P and Q . Let S and R be respectively the reflections of P and Q across altitude A D .
Being an isosceles trapezium, quadrilateral P Q R S is cyclic of course. Find the radius ρ of the circle circumscribing it.
Given: The altitude A D = 9 and circumradius of Δ A B C is 8 .
Report ρ 2 .
N o t e : An original twist to the famous problem! And by the way, the actual diagram looks not at all like the one shown here for guidance: Figure not to scale in the least!
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let O be the center of the circumcircle C T o f △ A B C . L e t C Q be the circumcircle of quadrilateral PQRS. I n r t ∠ d Δ D O B , ∠ D O B = C o s − 1 O B O D = 8 1 = 2 ∗ 4 1 . 4 1 = 2 ∗ α . ⟹ i n i s o s c e l e s △ O A B , ∠ O A B = α . ∴ A B = A D ∗ S i n α = 9 ∗ S i n 4 1 . 4 1 = 1 2 , ⟹ A M = M B = 6 . . ( 1 ) I n Δ C " C B , O D = 1 , a l s o O a n d D a r e m i d p i o n t s , ∴ B C " = 2 a n d ∥ O D ⟹ ∥ A D . S o ∠ M B C " = α . . . . . . A p p l y i n g C o s L a w t o Δ M B C " , M C " 2 = 2 2 . B u t M C " 2 = M Q 2 = 2 2 . . . MQ is the radius of C Q . . . ( 2 ) AD is the line of symmetry for both Δ A B C a n d q u a d r i l a t e r a l P Q R S . M is the midpoint of the chord AB of C T a n d a l s o o f c h o r d Q R o f C Q . S o ⊥ to the chords from M intersects AD, the line of symmetry at the common center O. So both cord distances from their common center a r e s a m e . ⟹ R a d i u s 2 − ( h a l f c h o r d ) 2 i s s a m e f o r b o t h . ⟹ O A 2 − A M 2 = ρ 2 − M Q 2 ∴ ρ 2 = 8 2 − 6 2 + 2 2 = 5 0
What an amazing solution! Kudos! I am in awe and admiration of the stark simplicity!
P.S. :No intention of nitpicking but in line 5, please correct the typo error A B = A D ∗ s i n α to A B = A D / s i n α
Log in to reply
Thanks for correction. Sorry I saw it only today.
I solved it almost the same way Aditya (but I did use the hint!LOL)
Apart from that: To find O H , an easier way is this: A H = 2 × O D
which in a way you have mentioned in your proof as well. ( C H = 2 × O M )
So, A H = 2
So, O H = 6 . Bingo!
Nice. I stretched that part a bit more.
By the way, why don't we meet sometime?!! You are from my city!
Problem Loading...
Note Loading...
Set Loading...
Solution:
( This proof : Because O is the circumcentre of the triangle, O P = O Q (can be proved by congruence of Δ O M Q and Δ O M P ) and by symmetry O Q = O R while O P = O S (because O lies on the symmetry line A D ) So, we have O P = O Q = O R = O S .) So, we basically need to find, say, O P .
( This proof : I hope it is known that ∠ A H B can be found by simple angle chasing as 1 8 0 − ∠ C which of course is the same as ∠ A C " B (cyclic quadrilateral C A C " B ). Now if ∠ H B C " comes out as ∠ C , our job is done as then H A C " B will be a p a r a l l e l o g r a m .
H o w ? : See F i g u r e 1 . ∠ A B L = 9 0 − ∠ A (in Δ A B L ).
∠ A C " C = ∠ B (both subtended by chord A C ) ⟹ ∠ A C C " is 9 0 − ∠ B (because Δ A C C " has ∠ C A C " = 9 0 because C C " is d i a m e t e r ),
But then ∠ A B C " = ∠ A C C " = 9 0 − ∠ B (angles subtended by chord A C " ). So, ∠ H B C " = ∠ A B H + ∠ A B C " = 9 0 − ∠ A + 9 0 − ∠ B = ∠ C . Q . E . D .
Now, the track is straight forward: Use:
This proof : Basically sum of two expressions for the diagonals using cosine rules; i.e. Apply cosine rule to find A C 2 in Δ A B C and then cosine rule in Δ B C D to find B D 2 and add the two equations. Use c o s ( 1 8 0 − θ ) = − c o s θ )
(It can be proved by similiarity of Δ M O G and Δ C H G where G is the centroid, and noting that C G = 2 × G M . We in herently use that H , G , O are collinear (Euler's line). So, now K H = O M .
Thus, K O M H is a parallelogram. Apply the result (1.). continuing the statement in (*)
So, O P 2 = O M 2 + M H 2 = 2 1 × ( O H 2 + M K 2 )
Note immediately that O C K M is also a parallelogram, so M K = O C = R , the circumradius. So, we update the above statement to:
Till now the acuteness or obtuseness of angle A did not matter. To find O H , it d o e s matter. Suppose on A D , the order of O , G , H be as in O P T I O N 1 in figure. However this is wrong, why? Because of the simple result:
Here, we say now, that the triangle is obtuse: So, H is closer to A than O . Now take O H as x . By the division in Euler's line segment : H G = 2 × G O , so H G = 3 2 x and G O = 3 x . So, A G = 3 2 x + 8 − x = 3 2 4 − x , G M = 3 x + 1 = 3 x + 3
Now, A G = 2 × G M ⟹ : 2 4 − x = 2 x + 6 ⟹ x = 6 .
Using (**), O P 2 = ρ 2 = 5 0 .